Analisis Kemampuan Penalaran Matematis Siswa dengan Menggunakan Model Pembelajaran Berbasis Masalah - Pniel Sozawato Zendrato; Netti Kariani Mendrofa; Yulisman Zega; Yakin Niat Telaumbanua (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Learning processes and daily life are significantly influenced by reasoning ability. Specifically, in mathematics education, reasoning is crucial for students to master. Reasoning plays a vital role in the development of mathematical thinking, serving as a foundation that enables students to delve into and understand general mathematical concepts and to draw conclusions from mathematical problems. By applying a problem-based learning model, students can be assisted in solving mathematical problems related to current issues. This study uses a qualitative approach with a phenomenological perspective, aiming to analyze and describe students' mathematical reasoning abilities through the problem-based learning model. The research was conducted at SMP Negeri 4 Gunungsitoli Utara. The results showed that after the reasoning ability test, student scores varied, with the highest score being 87, the lowest 31, and an average of 63.35, categorized as moderate. The analysis identified several factors affecting students' reasoning abilities, including lack of conceptual understanding, inconsistency in problem identification, lack of precision, and difficulty in finding formulas to solve problems.